The Light Bulb Went on: A Historiography-Based Approach to Disentangling Audio Description's Influential U.S. Roots From Its Common Practices. (July 2022) - Koirala, Sajja; Oppegaard, Brett
Introduction: American media-accessibility pioneers in the 1970s and 1980s not only sparked interest in the academic study of audio description, they also originated many practical techniques, protocols, theoretical perspectives, guidelines, and standards that persist in the fabric of this type of work decades later. In this study, we located and analyzed source documents for two oft-mentioned innovators—Gregory Frazier and Margaret Pfanstiehl—to shine light on their individual perspectives through a historiography of their foundational writings and associated media.Method: This analysis was conducted on publicly available source documents, such as Frazier's landmark thesis and also included a trove of Pfanstiehl's personal correspondence, as a way to establish particular points of theoretical and historical interest.Results: We found that despite the prominent place of Frazier and Pfanstiehl in audio description lore, neither actually published much writing about what they did and why they did it. Some of what they wrote has been selectively repeated, but other parts have been forgotten. In that respect, this research method could be used to more precisely trace and identify where particular practices emerged, under which theoretical perspectives, and complications. It also can help to show how these ideas were documented and tested during their emergence and domestication, as a way to gauge procedural rigor as well as validity of related findings.Discussion: Audio description scholarship needs theoretical anchors, but it also needs systematic testing of assumptions inherent in those theoretics, which this study helps to identify.Implications for Practitioners: Audio describers invariably will encounter the moment when an assertion of "this is the way we do it" collides with the curiosity of "why?" To promote best practices, the field has to understand where practices came from, how they developed, and as Frazier recommended, put those ideas to "objective" tests.